Number, causes and destinations of horses leaving the Australian Thoroughbred and Standardbred racing industries. Issue 8 (23rd June 2014) - Thomson, PC; Hayek, AR; Jones, B; Evans, DL; McGreevy, PD
<x xml:space="preserve">Abstract</x> Objective Significant proportions of horses leave the Australian Thoroughbred and Standardbred racing industries, which has ramifications for both the economic sustainability and the public perception of racing. The aim of this study was to quantify potential horse wastage, describe the destinations of exiting horses and identify risk factors for horses going to these destinations. Methods Questionnaires were sent to 1258 selected Thoroughbred and 981 Standardbred trainers, with response rates of 30% and 32%, respectively. The survey investigated the role of various risk factors for wastage, including horse age, sex and number of years in training. The destination of departing horses was also examined in relation to these risk factors. Results Total horse exit rates for the 2002–03 official race year were 39.7% and 38.7% for the Thoroughbred and Standardbred racing industries, respectively. Reasons for leaving included 'poor performance/slow' (36.5% Thoroughbreds, 35.2% Standardbreds), 'illness/injury' (31.0%, 27.1%), 'to breed' (9.4%, 10.1%), 'unsuitable temperament/behaviour' (6.4%, 6.4%) and 'other' (16.8%, 21.2%). Statistically significant (P < 0.001) risk factors influencing the destinations of both Thoroughbred and Standardbred racing horses included whether the trainer owned the horses, sex, age and reasons for leaving. In addition, some factors were specific to one breed or the other. Conclusions Improved behaviour training and early identification of the causes of poor performance could assist in reducing wastage.